2005
DOI: 10.1055/s-2005-865672
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Injury During Open Heart Surgery - Controlled Prospective Study

Abstract: There are no reports in the literature of routine preoperative and postoperative electrophysiological studies in large patient groups to evaluate brachial plexus injury during open heart surgery. It is known that heart surgery sometimes causes partial brachial plexus injury, especially in the lower trunk. However, these peripheral nerve problems are usually not considered clinically important and are not investigated. Patients undergoing open heart surgery must be closely followed up for peripheral nerve injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…23 Such a discrepancy may be due to the use of different retractor sizes between the studies. To further stratify these patients, Canbaz et al 24 demonstrated that 14% of patients undergoing coronary artery bypass and 8% of patients following open valve surgery had evidence of a brachial plexus injury. These rates may be higher in older patients, in the setting of longer operative times, and with internal mammary artery harvesting due to asymmetric retraction of the sternal halves.…”
Section: Surgical Equipmentmentioning
confidence: 99%
“…23 Such a discrepancy may be due to the use of different retractor sizes between the studies. To further stratify these patients, Canbaz et al 24 demonstrated that 14% of patients undergoing coronary artery bypass and 8% of patients following open valve surgery had evidence of a brachial plexus injury. These rates may be higher in older patients, in the setting of longer operative times, and with internal mammary artery harvesting due to asymmetric retraction of the sternal halves.…”
Section: Surgical Equipmentmentioning
confidence: 99%
“…[219][220][221] Exacerbation of preexisting disorders, such as affective (bipolar) and personality disorders, is also not unusual. 226 First rib fractures are often noted by bone scan, although they are frequently missed by routine chest x-rays. Cognitive behavior therapy and support stress management are helpful in alleviating postoperative depression.…”
Section: Preventionmentioning
confidence: 99%
“…Brachial plexus neuropathies were detected by electromyography and nerve-conduction tests in 37.7% of patients after coronary artery bypass grafting [Seyfer 1985]. Other studies found that patients with an injured brachial plexus were older and had undergone surgeries of longer duration [Canbaz 2005] and that the nerve plexus was most at risk for pathologic injury during retraction of the sternum for internal mammary artery harvest [Jellish 1994]. Sternal fracture was associated with the use of sternalretraction devices for internal mammary artery harvesting in coronary bypass procedures [Moore 1994].…”
Section: E489mentioning
confidence: 99%